2002
DOI: 10.1080/003655902317259292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluid and Dobutamine Treatment on Renal Function during Partial Superior Mesenteric Artery Occlusion and Reperfusion

Abstract: Intestinal ischaemia caused by partial SMA occlusion did not influence renal function. On the contrary, SMA reperfusion resulted in a significant impairment of renal function both in ischaemic and sham operated animals. The impairment was most obvious in control groups and in animals treated with dobutamine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Investigators have reported divergent results for other species. In dogs, 44 pigs, 45 and humans, 46,47 dobutamine infusion did not increase GFR or renal blood flow in adult patients or healthy volunteers. Conversely, studies in newborn pigs 48,49 and human neonates 50 revealed an increase in renal arterial blood flow in response to dobutamine infusion.…”
Section: Discussionmentioning
confidence: 79%
“…Investigators have reported divergent results for other species. In dogs, 44 pigs, 45 and humans, 46,47 dobutamine infusion did not increase GFR or renal blood flow in adult patients or healthy volunteers. Conversely, studies in newborn pigs 48,49 and human neonates 50 revealed an increase in renal arterial blood flow in response to dobutamine infusion.…”
Section: Discussionmentioning
confidence: 79%
“…Several researchers have shown that hepatic and pulmonary dysfunction may occur after mesenteric I/R [1,9]. However, the effect of mesenteric I/R on the kidney has received relatively little attention [14–19]. LaNoue et al.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of intestinal I/R on lipid peroxidation in rat kidney tissue has not been thoroughly investigated. Accumulating evidence suggests that renal dysfunction may occur after intestinal I/R [14–19]. In the present study, we investigated (1) the presence of oxLDL in renal tissue after intestinal I/R and (2) the association between oxLDL and iNOS expression and superoxide dismutase (SOD) activity in renal damage.…”
Section: Introductionmentioning
confidence: 99%